Generalizing Convolutional Neural Networks For Pattern Recognition Tasks - Ahmad Radzi, Syafeeza; Hani, Mohamed Khalil; Hindustan, Imran; Mat Ibrahim, Masrullizam; Wong, Yan Chiew (Asian Research Publishing Network (ARPN), 2015)
-